The immune-related fatty acids are responsive to CO2 driven seawater acidification in a crustacean brine shrimp Artemia sinica. (April 2018) - Gao, Yan; Zheng, Shu-cheng; Zheng, Chao-qun; Shi, Yue-chen; Xie, Xiao-lu; Wang, Ke-jian; Liu, Hai-peng
Abstract: The gradual increase of CO2 concentration in the atmosphere, absorbed by the ocean surface water through air to sea equilibration termed ocean acidification (OA), leads to the decline of pH in seawater. It is not clear so far how the composition of fatty acids, particular the immune-related, in marine crustacean and the subsequent energy supply in marine ecosystem are affected by OA. The brine shrimp Artemia sinica is an open and common feed that provide essential fatty acids for mariculture. In this study, the fatty acids profiles of brine shrimp cultured under different lower pH levels of CO2 driven seawater were investigated. The results showed a significant reduction of the proportion of total saturated fatty acids under the pH7.6 within one week. Meanwhile, the percentage of total monounsaturated fatty acids was significantly decreased at day 14 under pH7.8, and this percentage gave a significant increase of proportion within one week under pH7.6. Furthermore, the relative content of total polyunsaturated fatty acids (PUFAs) was found to be clearly increased with exposure to different seawater acidification at day 1, suggesting that the brine shrimp immune response was likely to be affected by acidified seawater as the PUFAs have been well known to be involved in immunomodulatory effects through alterations on cell membrane fluidity/lipid mediators and gene expression of cell signaling pathways. Notably, eicosapentaenoic acid and docosahexaenoic acid, which have essential effect on various physiological processes such as inflammatory cytokines production and cell structural stability, were strongly increased under two lower pH treatments within one week and with the significant increase at day 1 under pH7.6. These data clearly supported the hypothesis that OA might affect fatty acids composition, likely also the innate immunity, in crustacean and the subsequent energy transfer by food-chain system in the marine ecosystem. Highlights: The composition of fatty acids was clearly altered by seawater acidification in brine shrimp. The immune-related fatty acids were responsive to seawater acidification in brine shrimp. Physiology like the metabolism of fatty acids in crustacean was indeed affected by CO2 driven seawater acidification.